MULTI ETHICAL PROBLEMS DALAM BISNIS MULTI LEVEL MARKETING (Studi Kasus Akun Facebook WW) - Budhi Widi Astuti (Universitas Kristen Satya Wacana, 2016)
The question of ethics in the business activities of multi level marketing (MLM) becameone of the things seized enough attention. This is due to the applied practices affecting theprinciple of ethical or unethical.This research seeks to reveal multi ethical problems that appear in the content of themessage communication Facebook account WW by using qualitative researchmethodology. The content of messages is analyzed with a qualitative content analysismethods, while the case studies were chosen because researchers focus on one Facebookaccount, that belongs to the WW is MLM businesses PT HWI. Although the assessment ofethical and unethical it cannot be measured independently valid, but researchers trying toexpose some important aspects in the economic aspect, namely, business, legal, and moral.Then analyzed using the concepts of ethical utilitarianism. As a result, there are threefindings in ethical problems.Keywords: Multi Ethical Problems, Multi Level Marketing, Business Ethic, Facebook